Perancangan Sistem Informasi Persediaan Barang Menggunakan Visual Basic 2010 (Vb.Net) Pada PT. Solusi Rekatama Makmur - Rejeki, Sri; Ismasari Nawangsih; Setiawati, Siti (Program Studi Informatika, Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2021)
The warehousing management system is a key in the supply chain, where the main objective is to control all the processes that take place such as shipping and receiving. Currently the update of inventory data in PT. The Rekatama Makmur solution is periodically not updated every time a transaction occurs and is performed by a single computer performed by a warehouse officer, so that the other part of the employee is constrained in getting the latest data needed to make a business decision. Problems in this research how to make inventory information system for PT. Rekatama Makmur solution that produces updated inventory information every transaction and can generate information for warehouse officer, purchasing, and sales department. This research uses design and development which is done using VB.Net and MySql programming language as database management system.